ANALISIS FAKTOR YANG MEMPENGARUHI AKUNTABILITAS PENGELOLAAN DANA DESA PADA KABUPATEN KUANTAN SINGINGI : ANALYSIS OF FACTORS IMPACTING THE ACCOUNTABILITY OF VILLAGE FUND MANAGEMENT IN KUANTAN SINGINGI DISTRICT - Bahrul, Bahrul; Desmiyawati, Desmiyawati; Nurulita, Suci (Universitas Riau, 2023)
This study aims to analyze the factors that have an impact on village fund management accountability, which consists of internal control systems, financial report accessibility, community participation, and information technology utilization on village fund management accountability in Kuantan Singingi district. This study is aquantitative research. The population in this study is a village in Kuantan Singingi Regency, Riau Province. The sample in this research is a developing village in Kuantan Singingi, Riau Province and uses purposive sampling method. The type of data used in this research is primary data. Data collection techniques using a questionnaire. The analytical method used is Multiple Regression Analysis. The statistical findings of this study reveal that the factors of Internal Control System, Community Participation, and Information Technology Utilization impact the Accountability of Village Fund Management but not the Accessibility of Financial Reports. As a consequence, it is intended that this research will contribute to the growth of accounting literature, and that the findings would be useful to the Village Government in managing its strategic actions.